Nanomaterials in cancer immunotherapy: targeting cancer-associated fibroblasts - Zhongsong Zhang; Long Chen (Cancer Nanotechnology)
Abstract Emphasizing the significance of cancer-associated fibroblasts (CAFs), non-malignant yet pivotal players within the tumor microenvironment (TME), this review illuminates the role of inflammatory subtype (iCAF) as catalysts in cancer proliferation, metastasis, and therapeutic resistance. Given their paramount importance, targeting CAFs emerges as a robust strategy in the evolving landscape of cancer immunotherapy. Nanomaterials, distinguished by their unique features and malleability, hold considerable promise in biomedicine, especially in the precision-oriented domain of cancer therapy. Their aptitude for modulating immune responses, amplifying drug efficacy through precise delivery, and discerningly focusing on cells within the TME situates nanomaterials as formidable tools to transcend the boundaries set by conventional treatments. This review scrutinizes the convoluted interplay among CAFs, immune cells, and tumor cells within the TME. It further showcases widely utilized nanomaterials in cancer management. We underscore the potential of nanoscale drug delivery systems directed at CAFs, underscoring their transformative power in revolutionizing cancer therapies, enhancing precision, and culminating in improved patient outcomes.